2018
DOI: 10.18632/oncotarget.24157
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin inhibits gastric cancer invasion and metastasis by down-regulating Wnt/ASCL2 expression

Abstract: Achaete-scute-like 2 (ASCL2) is a transcription factor containing a basic helix-loop-helix (bHLH) domain and is a downstream target of Wnt signaling in intestinal stem cells. Bufalin is the primary active ingredient in Chan Su, a traditional Chinese medicine obtained from the skin and parotid venom glands of toads. The purpose of this study was to research the anti-invasion and anti-metastasis activity of bufalin in gastric cancer and to identify the potential mechanism. Bufalin inhibited gastric cancer cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…We have observed the inhibition of GSK3α and β-catenin by the activation of a destructive complex and further enhancing the deregulation of c-Myc and cyclin D1, stimulating cell death. In the current study, our results confirm strophanthidin's importance in the inhibition of Wnt/βcatenin signaling, and this activity was correlated with earlier reports suggesting that bufalin inhibits Wnt/β-catenin signaling in gastric cancer cells to induce apoptosis (69). However, this is the first report to show the role of strophanthidin in Wnt/βcatenin signaling and its downstream target genes.…”
Section: O21supporting
confidence: 92%
“…We have observed the inhibition of GSK3α and β-catenin by the activation of a destructive complex and further enhancing the deregulation of c-Myc and cyclin D1, stimulating cell death. In the current study, our results confirm strophanthidin's importance in the inhibition of Wnt/βcatenin signaling, and this activity was correlated with earlier reports suggesting that bufalin inhibits Wnt/β-catenin signaling in gastric cancer cells to induce apoptosis (69). However, this is the first report to show the role of strophanthidin in Wnt/βcatenin signaling and its downstream target genes.…”
Section: O21supporting
confidence: 92%
“…Few recent studies have reported the role of AHNAK in GC. However, studies have indicated that the AHNAK gene was closely related to the Wnt signaling pathway [12,16], and the Wnt signaling pathway was suggested to be closely associated with the development of GC [17,18]. We have shown that the AHNAK gene was a direct target gene of miR-93-5p in GC.…”
Section: Down-regulation Of Mir-93-5p Inhibits Activation Of the Wnt mentioning
confidence: 80%
“…It is also documented that Wnt signaling pathway also known as Wnt/β-catenin signaling pathway since it can regulate β-catenin protein levels therefore activating the Wnt, which could regulate Frizzled-1/β-catenin signaling pathway [30]. Dysregulation of Wnt signaling is observed in various human disease including GC, which is usually associated with the development stage of human cancers [17,18,31,32]. Besides miR-93-5p, other miRNAs including miR-139-5p may regulate Wnt-related factors, which could directly target the Wnt/β-catenin signaling pathways related Wnt-1 and suppress the expression of Wnt-1 and β-catenin [33].…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin can attenuate transforming growth factor-β (TGF-β)-induced upregulation of N-cadherin, vimentin, and Snail while downregulating E-cadherin by targeting hypoxia-inducible factor-1α (HIF-1α) [76]. In addition, the regulating of motility and invasiveness of cancer cells may be related to the PI3K/AKT/mTOR pathway [76, 81], Wnt/β-catenin pathway [66, 77], Hedgehog signaling pathway [67, 82], and etc.…”
Section: Molecular Mechanisms Of Anti-tumor Activitymentioning
confidence: 99%